Sessile Serrated Lesions: Searching for the True Prevalence and Risk Factors in China - Bing-Yue Yao; Li Zhang; Chuan-Xia Wu; Liang Zheng; Ben-Song Duan; Qin-Wei Xu; Jing-Jing Lian; Hai-Bin Zhang; Yu Wang; Jia Cao (The Turkish Journal of Gastroenterology)
Background/Aims: Growing recognition identifies sessile serrated lesions (SSL) as colorectal cancer (CRC) precursors. However, the SSL detection rate remains debatable and lacks a definitive consensus. Additionally, understanding the influencing factors in SSL development is limited. We aim to retrospectively analyze the true prevalence and risk factors of SSL in China.